Newly diagnosed type II diabetes mellitus presenting with localized itch - Mearza, Talib; Amer, Wesam Abou; Jaber, Maryam Al (International Journal of Research in Medical Sciences, 2020)
Type II diabetes is caused by insulin resistance resulting in high blood sugar levels. Although the typical symptoms of diabetes are described as polyuria, polydipsia and fatigue as many as 60% of newly diagnosed patients with type II diabetes are asymptomatic. Here authors present a case of a 39-year-old male patient who presented with localized pruritus affecting the medial aspects of his forearms and upper legs as the sole symptom of newly diagnosed type II diabetes mellitus. The itch symptom markedly improved on significantly reducing his dietary intake of sugars and with the use of metformin. Authors hope to alert clinicians to consider the possibility of underlying diabetes in such presentations to enable swift diagnosis and consequent treatment. It is unusual to find patients presenting with localized itch without any corresponding cutaneous manifestations as a presentation of type II diabetes.